Die retoriese analise van die Brief aan Filemon in die lig van Johannes Chrysostomus se homilieë oor dié brief - Tolmie, D. F. (HTS teologiese studies, 2014)
The rhetorical analysis of the Letter to Philemon in the light of John Chrysostom ‘s homilies about this letter. The study of Paul’s Letter to Philemon benefitted from the renewed interest in the rhetorical analysis of New Testament writings in recent times, in the sense that a large number of rhetorical studies of the letter have been published. These rhetorical analyses of the letter have been done from various perspectives, but until now no one has systematically investigated the way in which John Chrysostom interpreted the letter rhetorically in his three ‘Homilies on Philemon’. Accordingly, the study offers a detailed investigation of this issue. It is shown that John Chrysostom identified several important rhetorical aspects that have been neglected by modern scholars – aspects which could be used to enhance current interpretations of the rhetoric of the letter.